Determining the Distinguishing Features of Different Eating Action Types in Germany Using a Mixed-Method Approach - Lampmann, Lyn; Emberger-Klein, Agnes; Menrad, Klaus (Frontiers in Nutrition, 2021)
Food-related behaviour is a very complex topic, as it affects the most diverse areas of life. Accordingly, wide varieties of disciplines have already dealt with the topic to understand it better. The result is that there is neither a uniform nutrition knowledge nor a uniform nutrition behaviour. In order to reduce the complexity of a field of study, there is the methodical means of type-building. Both commercial and academic studies have already formed nutrition types, either by means of standardised questionnaires or with a specific content focus. However, since both individual and social aspects influence food-related behaviour, we investigate how people integrate eating into their everyday life against the background of (competing) individual and social demands by focusing on the individual point of view, for which a mixed methods approach is used. Based on 42 semi-structured, problem-centred interviews conducted in Germany in 2017, we built qualitative food-related types in a first step, which are analysed in this article using a quantitative content analysis and cross-over analysis to identify the particular distinguishing feature(s) of each type and test them for significance. The results show the prominent characteristics for each type and indicate furthermore that subjectivization, self-determination, the body as an instrument of power, adaptation to the environment and being overstrained with the own behaviour are particularly prominent when it comes to eating. Moreover, we clearly identified The Overstrained and The Relaxed as independent eating action types, which we could not find anywhere else. The study shows that interventions, especially for The Overstrained and The Controlled, are necessary to achieve a relaxed approach to eating in everyday life. At the same time, systematic approaches should be used to intervene in cases of overstraining or controlled behaviour.